Adverse Childhood Experiences, Mental Health, and Risk Behaviors Among Men in the Solomon Islands. (September 2018) - Lui, Paraniala Silas C.; Dunne, Michael P.; Baker, Philip; Isom, Verzilyn
Compared with many parts of the world, there has been little research in Pacific Island nations into the effects of adverse childhood experiences (ACEs) on adult health. This is a significant gap for local evidence-based child protection. We describe findings from a survey of 400 men aged 18 to 70 years recruited from randomly sampled households in Honiara city, Solomon Islands. Most men reported multiple adversities during childhood (80.7% 3 or more; 46% 5 or more), such as exposure to community and domestic violence, bullying, physical maltreatment, and sexual abuse. Men with multiple ACEs had significantly lower well-being and more psychological distress, recent stressful life events, and health risk behaviors. This study reports the first observation that betel quid chewing increased as a function of multiple ACEs. In comparison with recent East Asian studies, the Solomon Islands data suggest that the collective geographic category of "Asia-Pacific" masks significant intraregional differences in childhood adversities.